Nail-stem construct method for periprosthetic humeral fractures with recalcitrant nonunion after total elbow arthroplasty: A surgical technique - Yen-Sheng Chiang; Shih-Hao Chen; Keng-Chang Liu; Chang-Chen Yang; Jui-Teng Chien (Tzu Chi Medical Journal)
Objectives: The objective of this study was to describe the surgical technique using an innovative nail-stem construct in treatment of periprosthetic humeral fractures with recalcitrant nonunion after total elbow arthroplasty (TEA). Materials and Methods: Patients diagnosed with humeral recalcitrant nonunion in periprosthetic fractures and stem loosening after TEA were retrospectively recruited between 2018 and 2019. The demographic data and related clinical outcomes were recorded. We use a cutting length of the nail pushing into the humeral canal and then pull back distally to dock the tip of the humeral stem. The cement was packed into the humeral canal, and the periprosthetic bone defect was impacting with harvested allograft chip. Results: Patient age, gender, lesion site, number of previous surgeries, and the time period from the primary TEA to the nail-stem reconstruction were allocated. Moreover, the range of motion, degree of elbow stability, and level of pain were evaluated for each patient following this procedure. All the four patients achieved an optimal range of motion and secure stability with painless elbow at final follow-up. Conclusion: Our proposed nail-stem construct with double allogenous bone plate is a feasible alternative for revisional TEA in patients with implant loosening, periprosthetic humeral fractures, and recalcitrant nonunion.